Consensus-based leader-following formation control for a group of semi-biomimetic robotic fishes. (13th July 2017) - Zhang, Shouxu; Yan, Weisheng; Xie, Guangming
In this article, we developed a consensus-based leader-following formation control algorithm for a group of robotic fishes modeled by Euler–Lagrange dynamics. The Euler–Lagrange dynamics has been simplified as a second-order dynamics using the input transformation technique. Two consensus-based formation control strategies are discussed under the scenario: (1) leader with constant velocity and (2) leader with time-varying velocity. Three formation-keeping examples are shown in the simulations to verify the obtained formation control algorithm.